Application of Multiplex RT-PCR for Detection of Cucurbit-infecting Tobamovirus - Budi Setiadi Daryono; Keiko T. Natsuaki (Universitas Gadjah Mada, 2011)
Cucumber green mottle mosaic virus (CGMMV) and Kyuri green mottle mosaic virus (KGMMV) are seed borne viruses and they are also transmitted mechanically during agricultural practice and through water. Hence, these viruses have potential diseases widely distributed throughout the world. To detect different strains of CGMMV and KGMMV, several specific primers for each virus were designed for single and multiplex RT-PCR. The results of single and multiplex RT-PCR showed that CGMMV was detected in zucchini isolated in Bali-Indonesia, while KGMMV was detected both in zucchini isolated in Bali-Indonesia and Cucumis metuliferus isolated in Thailand. Furthermore, artificial co-infection of these two viruses was prepared and carried out using two different ways of viral RNAs extraction. Based on the results, it could be reported that viral RNAs for cDNA amplification by multiplex RT-PCR could be extracted from a mixture of infected leaves or separate extraction of each viruses infected leaves. In addition, results presented in this study demonstrated the application of multiplex RT-PCR to simultaneously detect CGMMV and KGMMV from cucurbit leaves using a mixture of four primers and its feasibility as a sensitive and rapid laboratory assay. Since, no multiplex RT-PCR technique has been described for the detection of CGMMV and KGMMV, this technique can be a good option for sensitive and reliable tool for detection of two major cucurbit infecting Tobamoviruses.Keywords : Cucurbit infecting Tobamovirus, multiplex RT-PCR, seed borne viruses